International Monetary Fund Annual Report 2020. (Annual Report of the Executive Board, 2020)
This year, as the world faced a crisis like no other, the International Monetary Fund and its member countries swung into action to save lives and put a floor under the world economy. But the outlook remains uncertain. Countries now face a 'long ascent' that will be difficult, uneven, uncertain, and prone to setbacks. The IMF is working to help countries focus on "policies for people" to generate a transformational recovery through job-rich growth that benefits all.